Gambaran Konsumsi Gula, Garam dan Lemak Penduduk Dusun Batur Kidul Kecamatan Getasan Kabupaten Semarang - R.L.N.K. Retno Triandhini; Monika Rahardjo; Magdalena Putranti (Journal of Health (JoH), 2018)
The prevalence of non-contagious diseases such as diabetes mellitus, hypertension and obesity are increasing from year to year. Unhealthy diet such as excessive consumption of sugar, salt and fat is one of the factors causing these diseases. The result of data analysis shown that 21.5% of respondents had consumed sugar exceeding the recommendation of Permenkes no 30 year 2013 (>50 gram/day), 73.7% of respondents consume salt exceeding the recommendation of Permenkes no 30 year 2013 (5 gram/day), and as many as 7% of respondents consume fat exceeds the recommendation Permenkes no 30 year 2013 (> 67% gram /day). The highest consumption of salt and fat occurs in the age group of 56 - 65 years, while the highest sugar consumption occurs in the age group 40 - 45 years. Based on sex, women tends to consume sugar, salt and fat higher than men. Consumption of salt and sugar of respondents is high. This needs special attention because excessive salt and sugar consumption can cause non-contagious diseases such as hypertension and Diabetes Mellitus type 2, whose prevalence in Indonesia is increasing.